Food Safety Practices among Postnatal Mothers in Western Ghana - Stephen T. Odonkor; Napoleon Kurantin; Anthony M. Sallar (International Journal of Food Science)
Food safety has become a global issue due to the morbidity and mortality associated with it, particularly in developing countries. The objective of this community-based study is to examine food safety practices and its associated factors among postnatal mothers in the Western Region of Ghana. A cross-sectional survey study was conducted from August 1 2019 to January 31, 2020 from which data was obtained from the postnatal mothers (N=300). The data was analysed using SPSS v.23. The findings suggest that majority (86%) of the respondents exhibited good food handling practices. Also, 66.3% and 91.7% of the respondents exhibited good food preparation and proper storage practices, respectively. Results also revealed that the odds of performing good handling practice among respondents within the age group of 36-45 years were five times higher compared to those within the age group of 18-25 years [OR=4.92 (95% CI: 1.44–16.86), p=0.011]. Moreover, respondents who had tertiary education qualifications were more likely to have proper food handling practices compared to those with primary education [OR=0.27 (95% CI: 0.09–0.71), p=0.009]. These findings provide useful insights for policy directions. The government of Ghana and other stakeholders should develop a communication strategy to increase and sustain publicity and education on food safety particularly to postnatal mothers and the citizenry in general.